FGF21 is an insulin-dependent postprandial hormone in adult humans - Samms, Ricardo J.; Lewis, Jo E.; Norton, Luke; Stephens, Francis B.; Gaffney, Christopher J.; Butterfield, Tony; Smith, Dennis; Cheng, Christine; Perfield, James W.; Adams, Andrew C.; Ebling, Francis J.P.; Tsintzas, Kostas (Oxford University Press, 2017)
Context: Fibroblast growth factor 21 (FGF21) secretion has been shown to respond directly to carbohydrate consumption, with glucose, fructose and sucrose all reported to increase plasma levels of FGF21 in rodents and humans. However, carbohydrate consumption also results in secretion of insulin. Objective: The aim of this study was to examine the combined and independent effects of hyperglycemia and hyperinsulinemia on total and bioactive FGF21 in the postprandial period in humans, and determine whether this effect is attenuated in conditions of altered insulin secretion and action. Methods: Circulating glucose, insulin, total and bioactive FGF21 and fibroblast activation protein (FAPα) were measured in adults with and without type 2 diabetes (T2D) following an oral glucose tolerance test (OGTT), and under a series of insulin and glucose clamp conditions and following high fat diet in healthy adults. Results: Circulating total and bioactive FGF21 levels responded acutely to OGTT, and their ratio was attenuated in T2D patients with reduced postprandial insulin response. The clamp studies revealed that insulin but not glucose accounts for the postprandial rise in FGF21. Finally, there was an attenuated rise in FGF21 in response to a high fat dietary intervention that is known to alter insulin-stimulated substrate utilization in metabolically active tissues. Conclusions: Insulin rather than glucose per se increases total and bioactive FGF21 in the postprandial period in adult humans. Understanding the impact of T2D on bioactive FGF21 will have a significant effect upon the efficacy of therapeutic agents designed to target the FGF21 pathway.